Indonesian sharia tourism industry: opportunities & challenges towards sustainability / Nihayatul Maskuroh - Maskuroh, Nihayatul (Universiti Teknologi Mara Selangor, 2023)
The tourism sector is one of the sectors capable of increasing employment and economic growth. Currently, sharia tourism is starting to be in great demand. This is in line with the increase in Muslim tourists from year to year. An increase in Muslim tourists is both an opportunity and a challenge to be able to improve a sustainable sharia tourism sector in Indonesia. The purpose of conducting this research is to find out about the opportunities and challenges of the sharia tourism industry as well as the right strategy for the development of the Indonesian sharia tourism industry. This type of research is qualitative research using descriptive methods with data collection techniques in the form of documentation studies. Based on the research results obtained, the sharia tourism industry in Indonesia has good opportunities and potential as part of a sustainable national tourism industry. The tourism industry also contributes to increasing government revenues. In addition to having tourism potential, Indonesian sharia tourism has several challenges including demand and market aspects, technology and information aspects, regulatory aspects, financing aspects and research and development aspects.